Selenium as a therapeutic adjuvant for isoniazid/rifampicin-induced hepatotoxicity - Elias Adikwu; Ebinyo Clemente Nelson; Peter Fiyebo (BLDE University Journal of Health Sciences, 2020)
BACKGROUND: Isoniazid-rifampicin (INH-RIF) is used for the treatment of tuberculosis, but its hepatotoxicity is a serious health predicament. Selenium (Se) is a trace element with potential to safeguard cells from damage. AIM AND OBJECTIVE: This study assessed the potential of Se to prevent INH/RIF-induced hepatotoxicity in albino rats. MATERIALS AND METHODS: Forty-five adult male albino rats were randomly assigned to four groups. Group 1A (Placebo control) and Group 1B (Solvent control) were orally treated with normal saline (0.2mL) and corn oil (0.2mL) daily for 21 days, respectively. Group 2 (2A–2C) was orally treated with Se (0.1, 0.2, and 0.4 mg/kg) daily for 21 days. Group 3 was orally treated with INH-RIF (50/100 mg/kg) daily for 21 days. Group 4 (4A–4C) was orally pretreated with Se (0.1, 0.2, and 0.4 mg/kg) before oral treatment with INH-RIF (50/100 mg/kg) daily for 21 days, respectively. After treatment, the rats were weighed and anesthetized. Blood samples were collected and analyzed for serum liver function markers. Liver samples were weighed and analyzed for histology and biochemical indices. RESULTS: INH-RIF caused significant (P < 0.001) decreases in body weight, superoxide dismutase, glutathione, catalase, and glutathione peroxidase levels with significant (P < 0.001) increases in liver weight, malondialdehyde, alkaline phosphatase, aminotransferases, lactate dehydrogenase, gamma-glutamyl transferase, total bilirubin, and conjugated bilirubin levels, when compared to control. INH-RIF caused liver ischemic necrosis and vascular congestion. Hepatotoxicity induced by INH-RIF was abrogated in a dose-dependent fashion by pretreatment with Se 0.1 mg/kg (P < 0.05), 0.2 mg/kg (P < 0.01), and 0.4 mg/kg (P < 0.001) when compared to INH-RIF. CONCLUSION: Se may serve as an adjuvant treatment for hepatotoxicity caused by INH-RIF.